Differentiation of left ventricular deformation using 2D speckle tracking based on left ventricular geometric pattern in a hypertensive population: a single-center study - Mefri Yanni; Nani Nani; Wulan Prisilla (Arterial Hypertension)
BACKGROUND: Left ventricular (LV) adaptation to arterial hypertension can result in different geometric responses with different hemodynamic patterns. Different patterns of left ventricular geometry have a different impact on cardiovascular outcome. Using 2D speckle tracking echocardiography, this study investigated left ventricular mechanics in hypertensive patients with different geometric patterns by using two-dimensional (2DE) speckle tracking echocardiography. MATERIAL AND METHODS: This cross-sectional study was conducted on 94 patients who underwent a complete 2DE examination. The individuals were divided into three groups of LVH concentric remodeling, hypertrophy, and eccentric hypertrophy — linked to different clinical profiles, including age, gender, blood pressure, and medication use. RESULTS: This study examined 94 hypertensive patients, identifying three left ventricular geometry patterns: concentric remodeling, hypertrophy, and eccentric hypertrophy. With an average age of 56 years and more women than men, especially in certain groups, it found that those with concentric hypertrophy had higher systolic blood pressure. 2D speckle tracking echocardiography showed left ventricular strain decreased from the hypertensive patients with concentric remodeling, across the individuals with left ventricular concentric hypertrophy and eccentric hypertrophy LVH patterns. Reduced 2DE GLS was associated with LVH patterns (p = 0.05). CONCLUSION: In this study, concentric hypertrophy LV was the most observed left ventricular geometry pattern. Left ventricular deformation in hypertensive patients is significantly impacted by left ventricular geometry. Eccentric hypertrophy LV pattern has the greatest unfavorable effect on 2DE left ventricular mechanics. The classification of left ventricular geometry provides valuable and comprehensive information about left ventricular mechanical deformation and function in hypertensive population.